Clear Cell-Papillary Renal Cell Carcinoma of the Kidney Not Associated With End-stage Renal Disease: Clinicopathologic Correlation With Expanded Immunophenotypic and Molecular Characterization of a Large Cohort With Emphasis on Relationship With Renal Angiomyoadenomatous Tumor. (July 2015) - Aron, Manju; Chang, Elena; Herrera, Loren; Hes, Ondrej; Hirsch, Michelle S.; Comperat, Eva; Camparo, Philippe; Rao, Priya; Picken, Maria; Michal, Michal; Montironi, Rodolfo; Tamboli, Pheroze; et al.
Abstract : Clear cell-papillary renal cell carcinoma (CC-Pap RCC) is a recently described renal tumor initially reported in the setting of end-stage renal disease (ESRD). It has unique morphologic and immunohistochemical features that differentiate it from the more common clear cell RCC and papillary RCC. Recently, these tumors have also been described in a sporadic setting. We studied 64 cases of CC-Pap RCC not associated with ESRD (57 CC-Pap RCCs and 7 cases with features of renal angiomyoadenomatous tumors [RAT] including 5 initially diagnosed as such). The morphologic features of all cases and the immunohistochemical profile of 59 cases were studied along with the clinical and molecular features of 30 and 12 cases, respectively. All the tumors were well circumscribed with a mean tumor size of 2.6 cm and showed a wide array of architectural patterns, usually mixed, including tubular (77%), papillary (62%), tubulocystic (52%), and compact nested (21%). Seventy-three percent of the cases showed areas in which the tumor nuclei had a distinct orientation away from the basement membrane. Ninety-two percent of the cases had a low Fuhrman nuclear grade (nuclear grade 2%‐86%, and nuclear grade 1%‐6%); however, 8% cases showed foci of Fuhrman nuclear grade 3. In 4 cases, epithelial tumor comprised <5% of the tumor; >95% of the tumor was cystic or hyalinized. The stroma varied from being minimal to occasionally prominent myxoid to hyalinized and rarely with organized amianthoid fibers or well-defined smooth muscle bundles. Pathologic stage was reliably assigned in 60 cases, of which 93.3% (56 cases) were pT1, 3.3% (2 cases) were pT2, and 3.3% (2 cases) were pT3a with extension into the perinephric fat. One case had coagulative necrosis; sarcomatoid change and vascular invasion was not identified. The tumors showed a fairly typical immunoprofile characterized by positivity for CK7 (100%), HMCK (96%), CAIX (94%), and vimentin (100%) with negativity for AMACR, RCC, and TFE3; CD10 was positive in 24%. None of the cases tested showed recurrent chromosomal imbalances by virtual karyotyping, fluorescence in situ hybridization, or 3p loss of heterozygosity analysis. VHL gene mutations were, however, noted in 3 cases (2 in exon 1 and 1 in exon 3). Clinical follow-up information was available in 47% of the patients, with a mean and median follow-up of 47 and 37 months, respectively (range, 18 to 108 mo). One case occurred in the setting of VHL syndrome and multiple benign cysts. None of the cases showed local recurrence, metastasis, or death due to disease. Morphology, immunophenotype, and molecular studies did not vary between typical cases, those with prominent smooth muscle (so-called RAT), and historically published data on cases occurring in ESRD. Our analysis confirms that CC-Pap RCC is a unique subtype of adult renal epithelial neoplasia in which tumors are frequently small, are of low nuclear grade and pathologic stage, and have extremely favorable short to intermediate range prognosis. Tumors occurring sporadically, with prominent smooth muscle stroma (so-called RAT), and occurring in ESRD are in the spectrum of the same category of tumors. Abstract : Supplemental Digital Content is available in the text.